When historical minimalism becomes philosophical maximalism - Gericke, Jaco (Old Testament essays, 2014)
In this article the author takes a closer look at the turn to philosophy in the writings of some scholars associated with so-called historical minimalism (Thomas L. Thompson & Philip R. Davies). Whereas scholarly focus has tended to be on deconstructive aspects of the collapse of history this contribution looks at one constructive part thereof, namely the overlooked reappearance of what boils down to philosophical maximalism.